Political news and stock market reactions: Evidence from Turkey over the period 2008-2017 - Sleiman Karime; Özlem Sayilir (International Journal of Management and Economics, 2019)
The primary objective of the study is to examine the impact of political news (good and bad news) on the returns and volatility of Borsa Istanbul 100 Index (BIST-100). Sample data cover the period from January 2008 to December 2017. The main sample was divided into two subperiods to insulate the dominating impacts of both the 2008 Global Financial Crisis and 2013 Federal Reserve Tapering on Turkish stock markets. The daily stock market data were collected from the Electronic Data Delivery System (EVDS) web service, while political news headlines were collected from the Guardian newspaper. Different nonlinear volatility models (symmetric and asymmetric Generalized AutoRegressive Conditional Heteroskedasticity [GARCH]-type models) were used to model and estimate BIST-100 volatility in response to political news. The findings of the paper highlight four main results. First, there seems to be a significant impact of political news on the returns and volatility of BIST-100 index. Second, negative shocks derived from bad news tend to have a significant impact on the returns and volatility of BIST-100, while positive shocks derived from good news do not tend to have any significant impact on the returns, but decreased returns volatility. Third, political news, both good and bad, can affect stock return and stock return volatility in different directions, and this direction is time-varying. Fourth, the findings strongly reveal the presence of "Leverage Effect" in the returns of BIST-100 index. Therefore, one can say that political uncertainty is still a problem for the Turkish stock market.
Keywords: C22; G11; G12; G14; 650; uncertainty; shock; return; volatility; BIST-100; GARCH